The Impact of Fiscal and Political Decentralization on Local Public Investments in Indonesia - Krisztina Kis-Katos; Bambang Suharnoko Sjahrir (Institute for the Study of Labor (IZA), 2014)
We investigate the effects of the Indonesian decentralization and democratization process on budget allocation at the sub-national level. Based on panel data for 271 Indonesian districts for the years of 1994 to 2009, we address the determinants of local investment expenditures in public infrastructure in the sectors of education, health, and physical infrastructure. We find that after the dramatic expenditure decentralization of 2001, districts with relatively lower levels of public infrastructure started to invest more in these sectors. In contrast to the marked budgeting changes following fiscal and administrative decentralization, we find no consistent effects of the democratization process on local public investments. Our results reflect initial improvements in local targeting but show no evidence of increasing electoral accountability.
Keywords: H72; H75; 330; decentralization; democratic elections; budget allocation; Indonesia